Impaired innate immune alveolar macrophage response and the predilection for COPD exacerbations. Issue 9 (31st March 2014) - Berenson, Charles S; Kruzel, Ragina L; Eberhardt, Ellana; Dolnick, Ree; Minderman, Hans; Wallace, Paul K; Sethi, Sanjay
Abstract : Background: Alveolar macrophages (AM) in COPD have fundamentally impaired responsiveness to Toll-like receptor 2 (TLR2) and TLR4 ligands of non-typeable Haemophilus influenzae (NTHI). However, the contribution of innate immune dysfunction to exacerbations of COPD is unexplored. We hypothesised that impaired innate AM responses in COPD extend beyond NTHI to other pathogens and are linked with COPD exacerbations and severity. Methods: AMs, obtained by bronchoalveolar lavage from 88 volunteers with stable-to-moderate COPD, were incubated with respiratory pathogens (NTHI, Moraxella catarrhalis (MC), Streptococcus pneumoniae (SP) and TLR ligands lipopolysaccharide, Pam3 Cys) and elicited IL-8 and TNF-α were measured by microsphere flow cytometry. NF-κB nuclear translocation was measured by colorimetric assay. AM TLR2 and TLR4 expression was determined by immunolabeling and quantitation of mean fluorescent indices. Participants were monitored prospectively for occurrence of COPD exacerbations for 1 year following bronchoscopy. Non–parametric analyses were used to compare exacerbation-prone and non-exacerbation-prone individuals. Results: 29 subjects had at least one exacerbation in the follow-up period (exacerbation-prone) and 59 remained exacerbation-free (non-exacerbation-prone). AMs of exacerbation-prone COPD donors were more refractory to cytokine induction by NTHI (p=0.02), MC (p=0.045) and SP (p=0.046), and to TLR2 (p=0.07) and TLR4 (p=0.028) ligands, and had diminished NF-κB nuclear activation, compared with non-exacerbation-prone counterparts. AMs of exacerbation-prone subjects were more refractory to TLR2 upregulation by MC and SP (p=0.04 each). Conclusions: Our results support a paradigm of impaired innate responses of COPD AMs to respiratory pathogens, mediated by impaired TLR responses, underlying a propensity for exacerbations in COPD.